2006
DOI: 10.1088/0953-8984/18/19/008
|View full text |Cite
|
Sign up to set email alerts
|

Extended Finnis–Sinclair potential for bcc and fcc metals and alloys

Abstract: We propose an extended Finnis-Sinclair (FS) potential by extending the repulsive term into a sextic polynomial for enhancing the repulsive interaction and adding a quartic term to describe the electronic density function. It turns out that for bcc metals the proposed potential not only overcomes the 'soft' behaviour of the original FS potential, but also performs better than the modified FS one by Ackland et al, and that for fcc metals the proposed potential is able to reproduce the lattice constants, cohesive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
137
2
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(144 citation statements)
references
References 41 publications
4
137
2
1
Order By: Relevance
“…Most of the Ta potential models in the literature based on either EAM or FS parametrization schemes [17][18][19][20][21][22] were not specifically developed for high-pressure/high-temperature applications. As a result, high-pressure properties are reproduced with various degrees of success.…”
Section: Potential Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the Ta potential models in the literature based on either EAM or FS parametrization schemes [17][18][19][20][21][22] were not specifically developed for high-pressure/high-temperature applications. As a result, high-pressure properties are reproduced with various degrees of success.…”
Section: Potential Developmentmentioning
confidence: 99%
“…Employing the EAM models' EOS, we evaluated the P-T Hugoniot curve by solving the Rankine-Hugoniot equation, (21) treating the thermal pressure within the quasiharmonic approximation and ignoring directional anisotropy. Calculating the Hugoniot this way gives results that agree well with NEMD simulations in the OD region, indicating that the MieGrüneisen (M-G) formalism works well for this system for pressures below 200 GPa, and that plasticity and material inhomogeneities play no significant role in shock temperatures.…”
Section: B Hugoniot Temperaturesmentioning
confidence: 99%
See 1 more Smart Citation
“…MD simulations were carried out using LAMMPS [6] with the Extended Finnis-Sinclair (EFS) potential [7]. The monocrystal tantalum domain was a cube with a spherical void at the center.…”
Section: Methodsmentioning
confidence: 99%
“…At each thermodynamic state, the system is first equilibrated for 1 ns, and the physical quantities of interest were then accumulated for a time span of 5 ns, with a time step of 1 fs. In our MD simulations for Ta, the extended Finnis-Sinclair (EFS) potential proposed by Dai et al was employed, 26 which has been suggested to be a reliable potential for simulating melting curves and transport and structural properties of refractory metals. 10,11,27 The n-body Sutton-Chen EAM (Q-SC) potential was used to describe the interparticle interactions of late transition metals Fe, Ni, and Fe 0.9 Ni 0.1 alloy, 28 the mixing rule is used to get the mixing parameters between Fe and Ni.…”
Section: © 2017 Author(s) All Article Content Except Where Otherwismentioning
confidence: 99%